PENGARUH BIAYA BAHAN BAKU PRODUKSI, BIAYA PEMASARAN, BIAYA TENAGA KERJA TERHADAP RETURN ON INVESTMENT (ROI) CV PEPS ADVERTISING PANGKALPINANG - Deri Kusmadeni; Mohamad Makrus (MANAJEMEN DEWANTARA, 2023)
This research entitled the correlated of the cost of raw material production, marketing costs and salary costs on Return On Investment (ROI). The population in this study is the financial statements of CV. PEPS Advertising from 2020 to 2022. The sample in this research is a report of the costs of production raw materials, marketing costs, labor costs and monthly profit and loss of CV. PEPS Advertising for 3 years (36 months) in 2020 - 2022 (Time Series). The variables used in this study are the independent variables (the cost of raw materials for production, marketing costs and salary costs) and the dependent variable Return On Investment (ROI). This research used analysis tools, namely: normality test, multicollinearity, heterokedacity test, multiple linear regression with t test, F test and coefficient of determination. The results of this research stated that simultaneously variable costs of raw materials for production, marketing costs and salary costs correlated the Return On Investment (ROI). Based on the t test that the variable costs of raw materials for production, marketing costs and salary costs correlated the Return On Investment (ROI) while the most dominant variable influencing the Return On Investment (ROI) is the marketing costs. This research can be concluded that there is an correlated of the cost of production raw materials, marketing costs, and salary costs simultaneously and partially on the Return On Investment (ROI) of CV PEPS Advertising Pangkalpinang.